1990
DOI: 10.1007/bf01208582
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of malate by cultured rat brain astrocytes

Abstract: Since malate is known to play an important role in a variety of functions in the brain including energy metabolism, the transfer of reducing equivalents and possibly metabolic trafficking between different cell types; a series of biochemical determinations were initiated to evaluate the rate of 14CO2 production from L-[U-14C]malate in primary cultures of rat brain astrocytes. The 14CO2 production from labeled malate was almost totally suppressed by the metabolic inhibitors rotenone and antimycin A suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
53
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 40 publications
14
53
0
1
Order By: Relevance
“…Since lactate has been proposed to have a role in metabolic trafficking from astrocytes to neurons in brain [3][4][5][6][7][8][9], we determined the effect of other compounds which are released by brain cells and/or thought to be involved in trafficking [33,41] on the rate of lactate uptake by synaptosomes (table 2). Addition of the amino acids glutamate, glutamine and aspartate had little or no effect on the rate of lactate uptake by synaptosomes.…”
Section: Uptake Of L-[u-14 C]lactate In the Presence Of Added Effectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since lactate has been proposed to have a role in metabolic trafficking from astrocytes to neurons in brain [3][4][5][6][7][8][9], we determined the effect of other compounds which are released by brain cells and/or thought to be involved in trafficking [33,41] on the rate of lactate uptake by synaptosomes (table 2). Addition of the amino acids glutamate, glutamine and aspartate had little or no effect on the rate of lactate uptake by synaptosomes.…”
Section: Uptake Of L-[u-14 C]lactate In the Presence Of Added Effectorsmentioning
confidence: 99%
“…A number of competition experiments were done since our group and others have demonstrated that both the uptake [20,25,26] and metabolism [7,26,[33][34][35] of energy substrates in brain tissue are regulated in part by the relative concentration of other key metabolites in the Values with asterisks are significantly different from the control value: * p ! 0.05; ** p !…”
Section: Uptake Of L-[u-14 C]lactate In the Presence Of Added Effectorsmentioning
confidence: 99%
“…It has been shown that malate can be oxidized as an energy source by cultured mouse brain astrocytes and to a lesser extent by neurons [1]. Furthermore, McKenna et al [2] proposed that the oxidation of malate in astrocytes occurs in multiple compartments and is significantly affected by a number of metabolites. The high rate of oxidative metabolism in the brain requires a very active glycolysis closely coupled to the TCA cycle, so that the reducing equivalents of NADH, generated during glycolysis, are transported across the mitochondrial membrane [3].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have documented uptake and oxidation of 14 C-labeled glycerol (McKenna et al 1986a), lactate (Brandt et al 1984;McKenna et al 1994), glutamine/glutamate (Yu et al 1984;McKenna et al 1994), citrate (Westergaard et al 1994), malate (McKenna et al 1994(McKenna et al , 1990, b-hydroxybutyrate (bHB) (Edmond et al 1987;McKenna et al 1994), acetoacetate (Lopes-Cardozo et al 1986;Waniewski and Martin 1998), as well as octanoate and palmitate (Edmond et al 1987). However, ketone bodies such as bHB are the only endogenously circulating alternative substrates that have been shown significantly to supplement cerebral metabolism (Owen et al 1967;Hawkins et al 1971;Dahlquist and Persson 1976).…”
mentioning
confidence: 99%